OGLE-2019-BLG-1470LABc: Another microlensing giant planet in a binary system?. Issue 2 (18th August 2022) - Kuang (匡仁昆), Renkun; Zang (臧伟呈), Weicheng; Jung, Youn Kil; Udalski, Andrzej; Yang (杨弘靖), Hongjing; Mao (毛淑德), Shude; Albrow, Michael D; Chung, Sun-Ju; Gould, Andrew; Han, Cheongho; Hwang, Kyu-Ha; Ryu, Yoon-Hyun; et al.
ABSTRACT: We report the discovery and analysis of a candidate triple-lens single-source (3L1S) microlensing event, OGLE-2019-BLG-1470. This event was first classified as a normal binary-lens single-source (2L1S) event, but a careful 2L1S modelling showed that it needs an additional lens or source to fit the observed data. It is found that the 3L1S model provides the best fit, but the binary-lens binary-source (2L2S) model is only disfavoured by Δχ 2 ≃ 18. All of the feasible models include a planet with planet-to-host mass-ratios 10 −3 ≲ q ≲ 10 −2 . A Bayesian analysis based on a Galactic model indicates that the planet is super-Jovian, and the projected host-planet separation is about 3 au. Specifically, for the best-fitting 3L1S model, the two stars have masses of M_1=0.57^+0.43_-0.32M_, and M_2=0.18^+0.15_-0.10M_ with projected separation of 1.3^+0.5_-0.5 au, and the planetary mass is M_3=2.2^+1.8_-1.3M_Jupiter . For the 2L2S model, the masses of the host star and the planet are 0.55^+0.44_-0.31M_ and 4.6^+3.7_-2.6M_Jupiter, respectively. By investigating the properties of all known microlensing planets in binary systems, we find that all planets in binary systems published by the KMTNet survey are located inside the resonant caustics range with q ≳ 2 × 10 −3, indicating the incompleteness of the KMTNet sample for planets in binary systems. Thus, planets in binary systems cannot be included in the current study of the KMTNet mass-ratio function, and a systematic search for planetary anomalies in KMTNet microlensing light curves of binary systems is needed.